Filling the Data Gap – A Pressing Need for Advancing MPA Sustainable Finance - Bohorquez, John J.; Dvarskas, Anthony; Pikitch, Ellen K. (Frontiers in Marine Science, 2019)
Reaching protected area (PA) coverage goals is challenged by a lack of sufficient financial resources. This funding gap is particularly pervasive for marine protected areas (MPAs). It has been suggested that marine conservationists examine examples from terrestrial protected areas (TPAs) for potential solutions to better fund MPAs. However, the funding needs for MPAs and TPAs have not been directly compared, and there is risk of management failures if any such differences are not properly considered when designing MPA financial strategies. We perform an in-depth literature review to investigate differences in distribution of costs incurred by MPAs and TPAs across three primary categories; establishment, operational, and opportunity costs. We use our findings to conduct a snapshot quantitative comparison, which we complement with theoretical support to provide preliminary insight into differences between MPA and TPA costs, and how these may influence financial strategies most appropriate for each type of PA. Our research suggests that TPA costs, and thereby funding requirements, are greater for the time period leading up to and including the implementation phase, whereas MPAs have higher financial requirements for meeting long-term annual operational costs. This may be primarily due to the prevalence of private property rights for terrestrial regions, which are less frequently in place for ocean areas, as well as logistical requirements for enforcement and monitoring in a marine environment. To cement these suggestions in greater analytical certainty, we call for more thorough and standardized PA cost reporting at all stages, especially for MPAs and PAs in developing countries. The quantity and quality of such data presently limits research in PA sustainable finance, and will need to be remedied to advance the field in future years.